Existence and Multiplicity of Positive Solutions for Schrödinger-Kirchhoff-Poisson System with Singularity. (23rd April 2017) - Mu, Mengjun; Lu, Huiqin
Abstract : We study a singular Schrödinger-Kirchhoff-Poisson system by the variational methods and the Nehari manifold and we prove the existence, uniqueness, and multiplicity of positive solutions of the problem under different conditions.